(untitled) (Письма в ЭЧАЯ, 2024)
In this work, we investigate the Higgs-gauge couplings hVV (with V=W,Z) through different final states at leptonic colliders. In many SM extensions, these couplings could be modified as g_hVV=κ_Vg_hVV^SM, either via radiative contributions or due compositeness nature of the Higgs and/or gauge bosons. As a first step, by assuming that theHiggs-gauge couplings are SM-like (κ_V=±1), we consider the three final states at leptonic colliders h u u @ 250 GeV,hW^+W^- @ 500 GeV and ZW^+W^- @ 1 TeV(with h→ bb, Z→ jj and W^-→^- u); in order to identify κ_V sings via possible deviation of the cross section values with respect to the SM. Then, by considering that such a deviation in κ_V with respect to the SM can not be seen at HL-LHC, i.e., |δκ_V/κ_V|≈0.040.05, we explore these three processes in the signal case |κ_V|=1 to produce some kinematic variables distributions. This may affectthe cross section and the kinematic distributions, and tiny excess or lack in events could be reported.